2016
DOI: 10.3390/molecules21040421
|View full text |Cite
|
Sign up to set email alerts
|

Methods for Improving Aptamer Binding Affinity

Abstract: Aptamers are single stranded oligonucleotides that bind a wide range of biological targets. Although aptamers can be isolated from pools of random sequence oligonucleotides using affinity-based selection, aptamers with high affinities are not always obtained. Therefore, further refinement of aptamers is required to achieve desired binding affinities. The optimization of primary sequences and stabilization of aptamer conformations are the main approaches to refining the binding properties of aptamers. In partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
140
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(143 citation statements)
references
References 72 publications
0
140
0
3
Order By: Relevance
“…This experimental process was repeated 3 times, and the K d (dissociation constant) was determined to be 100.9 nM. This value is much lower than those of several small molecule‐binding aptamers displaying affinities in the low to the midmicromolar range . Thus, this nanomolar K d value indicates that NPE‐01 has a high binding affinity for the target, NPE.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This experimental process was repeated 3 times, and the K d (dissociation constant) was determined to be 100.9 nM. This value is much lower than those of several small molecule‐binding aptamers displaying affinities in the low to the midmicromolar range . Thus, this nanomolar K d value indicates that NPE‐01 has a high binding affinity for the target, NPE.…”
Section: Resultsmentioning
confidence: 99%
“…The reason for the result against NP could be the similar hydrophobic sites of the 2 chemicals. The interaction between aptamer and target molecule is generally based on noncovalent bond, but hydrophobic interaction is limited by the low hydrophobicity of nucleic acids . But, the other result showed that the aptamer not only interact with ethoxylate chain which is the hydrophilic site of NPE.…”
Section: Resultsmentioning
confidence: 99%
“…Further refinement of aptamers is needed to achieve desired affinities [161]. Dimerization of aptamers (identical and different) was performed by Hasegawa and co-workers [162].…”
Section: Multivalent and Dimerization Of Aptamersmentioning
confidence: 99%
“…However, effective aptamer sequences are usually shorter than 30 nt, although they have typically been selected from libraries with 30–60 nt randomized nucleotides. Therefore, use of longer sequences in the selection library to increase the contact area is not an effective methodology . Linking of two aptamers that bind to different epitopes on the same protein target can generate hetero‐bivalent interactions and would be expected to increase the aptamer affinity greatly.…”
Section: Introductionmentioning
confidence: 99%